Effect of e-Commerce History on Consumer Perception: A comparative study of United States of America versus Vietnam - Tram, Pham Nguyen Bich; Rhee, Cheul; Kim, Jiyeol (Asia Pacific Journal of Information Systems, 2022)
Currently, Mobile-commerce is active around the world, and consumers' online activities have changed significantly from pc-base to mobile-base. Unlike IT advanced countries such as the United States, which experienced PC-based online commerce (hereafter, PC-commerce) before Mobile-commerce, developing countries such as Vietnam have a relatively short history of PC-commerce. Consumers' experience with PC-com-merce may affect their acceptance and use of Mobile-commerce. In this study, we tried to see if different online commerce histories differently affect consumers' online purchasing behavior. We selected the United States and Vietnam, with longer PC-commerce experience and shorter one, respectively. Data were collected for the following four groups: 1) the U.S. PC-commerce (n=256), 2) the U.S. Mobile-commerce (n=283), 3) the Vietnamese PC-commerce (n=159), and 4) the Vietnamese Mobile-commerce (n=225). As results, it was first confirmed that different e-commerce histories in developed and developing countries make the online shopping process different. Second, navigability has a huge impact on consumers' decision support satisfaction in Vietnam where PC-commerce history is shorter. Third, we identified that pre-purchase phase is more related with decision support satisfaction and that purchase phase is more related with task support satisfaction.
Keywords: Decision Support Satisfaction; E-Commerce; Mobile-Commerce; Pc-Commerce; Shopping Behavior; Task Support Satisfaction